Instrumental Competences: A case study in the field of linguistics - Herranz-Llácer, Cristina V.; Segovia Gordillo, Ana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper analyses the perception of traditional and online learning students regarding the degree of acquisition of instrumental competences concerning their university education in the field of linguistics. For this purpose, a sample of 182 students from Rey Juan Carlos University was used. The data were obtained through a questionnaire, and the results were compared in both groups. The impacts show that the students perceived that they had adequately acquired the competencies analysed and that critical reasoning and oral and written communication skills in the mother tongue showed significant differences according to the modality.